WAYS TO INCREASE ENTERPRISE SALES IN THE CONDITIONS OF DIGITALIZATION (Multidisciplinary Journal of Science and Technology, 2024)
Digitalization has revolutionized enterprise sales, reshaping traditional methods and introducing innovative strategies for customer engagement and revenue growth. This article explores how digital tools, platforms, and strategies, such as data analytics, omnichannel integration, and artificial intelligence, drive sales optimization. It highlights the transformative role of social media, influencer marketing, and augmented reality in creating immersive customer experiences. Additionally, the article addresses challenges like cybersecurity risks and competitive pressures while emphasizing the importance of adopting a proactive, data-driven approach.Through case studies and best practices, it provides actionable insights for leveraging digitalization to enhance enterprise sales performance. The findings underscore the need for agility, innovation, and customer-centricity to succeed in the evolving digital marketplace.